Trial of labor after one cesarean: role of the order and number of prior vaginal births on the risk of emergency cesarean delivery and neonatal admission - Tan, P.C.; Subramaniam, R.N.; Omar, Siti Zawiah (Elsevier, 2008)
Objective: To evaluate the influences of mode of immediate preceding delivery and number of prior vaginal births on the risk of repeat cesarean and neonatal admission at attempted vaginal birth after cesarean. Materials and Methods: We performed a retrospective study of the risk factors for emergency repeat cesarean delivery and neonatal admission in a trial of labor after prior cesarean section. The study comprised 342 women at term with at least one prior vaginal delivery in addition to one previous lower transverse cesarean. Clinical variables with crude p < 0.2 on Fisher's exact test for the defined primary outcomes of repeat cesarean and neonatal admission were included in the model for multivariable logistic regression analysis. Results: Cesarean as the immediate preceding mode of delivery (adjusted odds ratio, 5.3; 95 confidence interval, 2.5-10.8) was an independent predictor of emergency repeat cesarean delivery but not of neonatal admission. Higher parity of two or more previous vaginal deliveries compared with only one prior vaginal delivery was not associated with repeat cesarean or neonatal admission. Conclusion: In women who have had prior vaginal birth attempting a trial of labor after cesarean, a vaginal delivery before cesarean delivery is an independent risk factor for repeat cesarean. Women with two or more prior vaginal births have a similar risk for repeat cesarean and neonatal admission to women with only one prior vaginal birth. Taiwan J Obstet Gynecol 2008;47(3):305-311